Prevention Microbiological Using Functionalized Materials As Ecological Additives In Hygienic Paints - Arreche, Romina Andrea (2015)
At the present time one of the environmental challenges is the microbiological control in the indoor environment. The microorganisms that form biofilms on substrates located inside buildings and houses contribute to the formation of bio-aerosols when they are, partial or totally, dispersed and transported by the air. An example is the poisoning by certain fungal products as the mycotoxins (carcinogenic) that comes from fungi that can generally be in the interiors of buildings. Therefore, it is of vital importance contribute to avoid and/or minimize the microbiological growth in the indoor environments. In such sense the evaluation of new antimicrobial agents is fundamental and can be applied in diverse areas of development of protective coating and construction materials. The global efforts to reduce to dangerous remainders and technologically clean the chemical processes are being integrated with modern progresses as much in science as in the industry. In this investigation will work with remainders of seeds of sunflower functionalized with 3-aminopropyltriethoxysilane (APS), as support of additives, to a compound of Mo and K, that will act as antimicrobial, to be used in hygienic paintings. The originating solid of the sunflower seeds will be functionalized by means of reactions between organosilanes and the superficial groups of the mentioned solid. The characterization of synthesized solids will be made by means of SEM-EDS, DRX, FT-IR, textural properties, potentiometric titration, among others. These solids were microbiologically evaluated in front of fungi and bacteria, having given promissory results for novels ecological additives in hygienic paints.